MANAJEMEN PERUBAHAN DAN KINERJA PT GARAM DI KABUPATEN SUMENEP - Urmila; Kinanti Arifandyta Wardilla; Jumria; Iriani Ismail (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Change management plays a crucial role in improving company performance. This article analyzes the implementation of change management carried out by PT Garam in Sumenep Regency and its impact on the company's performance. Through a review of related news, it was found that PT Garam has undergone transformations in production, human resource development, and handling legal issues related to land. These efforts reflect PT Garam's commitment to achieving national salt self-sufficiency and improving the operational performance of the company.